Pengembangan multimedia pembelajaran Hukum Agraria pada Program Studi Pendidikan Kewarganegaraan Universitas Negeri Yogyakarta - Suripno, Suripno (Jurnal Civics: Media Kajian Kewarganegaraan, 2016)
This study was aimed at: 1) producing an appropriate learning multimedia for agrarian laws in terms of the material and presentation aspects student responses, and 2) investigate the effectiveness of the developed multimedia to develop student learning outcomes. This was a research and development study. The results of the study were as follows. 1) Regarding the developed learning multimedia product: a) it had good quality in terms of the material aspect with a mean score of 4.10; b) it had good quality in terms of the presentation aspect with a mean score of 4.07; and c) the students' responses to the media attractiveness showed that the multimedia was attractive with a mean score of 3.82. 2) The effectiveness of the use of the developed learning multimedia to improve learning outcomes was indicated by the fact that: a) there was a score improvement (30.16%) from a mean score of 51.50 in the pre-test to 73.75 in the post-test; and b) there was an improvement in mastery by 60% among 20 students, from five students (25%) attaining mastery in the pretest to 17 students (85%) attaining mastery in the posttest. Therefore, the multimedia for Agrarian Laws learning is appropriate to apply.